If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 10 + 2t + 4t Combine like terms: 2t + 4t = 6t 0 = 10 + 6t Solving 0 = 10 + 6t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6t' to each side of the equation. 0 + -6t = 10 + 6t + -6t Remove the zero: -6t = 10 + 6t + -6t Combine like terms: 6t + -6t = 0 -6t = 10 + 0 -6t = 10 Divide each side by '-6'. t = -1.666666667 Simplifying t = -1.666666667
| 6x+6=-120-10x | | 6-14= | | z^2+22+c= | | -7-5x=5x+16 | | 2x+7(3-4)=0 | | 60-2x=7x-8x | | 3(x-6)+2x=22-3x | | 3x+36=12x-36 | | 6f+24=-2f | | (2-x)*3=18 | | X+6=3(4+x) | | 1410-7x=20+23 | | x^2-30x-20=0 | | (-7)+(-20)= | | 8x+2=3x+12 | | 2b+-9=29 | | r^2-2rf-24f^2=0 | | -81-40x=7x+2 | | C=15(3n+8) | | (-5x^2+8)+(8x^2-6x+1)= | | (17x+9)+(8x+13)= | | 12n=6-3p | | 7(1.4+0.8y)-5y=26 | | 40-8v=-7(8v+8) | | 7(8h-3)+2h=72-4h | | (2x+3)(x+2)=10 | | 9(9+-4y)+36y=45 | | X+6=3(4+3) | | 5x+5-3(x-1)=7x+4-5 | | -9(16+-3y)+y=80 | | 26-x=3 | | 68-4x=9x+21 |